La gestión de la calidad y la prestación de servicios a los socios de la "Cooperativa de Ahorro y Crédito Minga Ltda.” – Riobamba - Mariño Tzacan, Moisés Eliseo (2022)
The following Investigation developed in the Cooperativa de Ahorro y Crédito "Minga" in order to propose a model of quality management in the provision of services that helps to increase the satisfaction of the members and that can be developed in all the branches, the review Biography develops the main theoretical foundations on quality management and service provision in the business sector, as well as the management models used worldwide, with this the state of the art was built, to carry out the diagnosis the main documents that define the policy and strategy of the Minga Savings and Credit Cooperative. I have carried out the interviews with the main managers and the surveys were applied to the members to know and identify the shortcomings that arise at the time of the provision of services, lastly, a quality management model for the cooperative based on the principles and taking into consideration the four phases for the improvement of quality and customer satisfaction, thereby becoming one of the most solvent financial entities with quality of services for the partners who are a fundamental part of the institution. With this, it was possible to conclude that the Cooperativa de Ahorro y Crédito Minga Ltda. Has some shortcomings within the institution that must improve optimally by solving the problems and taking into account all the recommendations given so that the organization can continue to remain in the market with high quality standards.